2017
DOI: 10.1530/edm-17-0041
|View full text |Cite
|
Sign up to set email alerts
|

Giant parathyroid adenoma: differential aspects compared to parathyroid carcinoma

Abstract: The 85% of cases of primary hyperparathyroidism (PHPT) are due to parathyroid adenomas (PA) and less than 1% to parathyroid carcinomas (PC). The PA usually measure <2 cm, weigh <1 g and generate a mild PHPT, whereas the PC usually exceeds these dimensions and are associated with a severe PHPT. However, giant PA (GPA), which is defined as those larger than 3 g, has been documented. Those may be associated with very high levels of PTH and calcium. In these cases, their differentiation before and after surgery wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…GPA tends to be reddish to brown and soft in consistency, which we have observed in our case. Microscopically, carcinomas differ from adenomas mainly because of their trabecular arrangement, dense fibrous bands (present in 90% of the cases), spindle shape of the tumor cells, presence of frequent mitotic figures (in 81% cases), capsular invasion (in 67% cases), and blood vessel invasion (in 12% cases) [4]. In our case, trabeculation and dense fibrous bands are not appreciated.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…GPA tends to be reddish to brown and soft in consistency, which we have observed in our case. Microscopically, carcinomas differ from adenomas mainly because of their trabecular arrangement, dense fibrous bands (present in 90% of the cases), spindle shape of the tumor cells, presence of frequent mitotic figures (in 81% cases), capsular invasion (in 67% cases), and blood vessel invasion (in 12% cases) [4]. In our case, trabeculation and dense fibrous bands are not appreciated.…”
Section: Discussionmentioning
confidence: 67%
“…GPA is considered when the tumor is larger than 3 grams. The suspicion of carcinoma is high if the tumor size is larger than 2 cm [4]. Diagnostic criteria in PA versus PC are not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…Parathyroid adenomas usually measure less than 2 cm and weigh less than 1 g. In parathyroid lesions larger than 2 cm, the differential diagnosis between giant parathyroid adenomas and parathyroid carcinomas would be considered [ 11 ]. Parathyroid cysts or cystic adenomas often show large parathyroid ones [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be concluded that in patients with giant parathyroid tumours with significantly high serum calcium, in the absence of symptoms, the likely diagnosis is giant parathyroid adenoma rather than parathyroid cancer. 5 However, this subject requires further evaluation.…”
Section: Case Seriesmentioning
confidence: 99%